THE INFLUENCE OF THE CONCENTRATION OF MONTMORILLONITE CONTAINING SORBENT AND pH OF THE CULTURE MEDIUM ON THE ANTIBIOTIC SENSITIVITY OF ESCHERICHIA COLI, S WELL AS THE EFFECT OF GROUND ON GROWTH OF ESCHERICHIA - Vladimir Bukhanov; Aleksandr Vezentsev; Olga Filippova; Sergey V. Nadezhdin; Olga Pankova; Tatyana Firsova; Mariya Mihaylyukova; Anton Tishin (Belgorod National Research University, 2017)
Diseases of a digestive tract in frequency and mass manifestation of young farm animals represent one of challenges for modern veterinary medicine. Giving chelators specific properties by immobilization on the surface of the medicinal substances in the form of active ligands is a promising direction to reduce side effects and increase treatment efficacy. The aim of this work was the comparative sensitivity test of E. coli to enrofloxacin and doxycycline and bactericidal action of montmorillonite containing sorbent and its combination with enrofloxacin, as well as the influence of the concentration of the enriched montmorillonite containing sorbent and pH of the culture medium on the antibiotic sensitivity of Escherichia coli. The sensitivity test of Escherichia coli to enrofloxacin, and the combination of enrofloxacin with sorbent was performd by the method of double serial dilutions of drugs in a liquid culture medium. The influence of the concentration of the enriched montmorillonite containing sorbent and pH of the culture medium on the sensitivity of E. coli to enrofloxacin and doxycycline was performed by diffusion method on Mueller-Hinton agar (MHA). Value of the bactericidal action of montmorillonite containing sorbent and its combination with enrofloxacin and expressing the sorption activity of the sorbent in relation to E. coli, were performed by confocal laser scanning microscopy (CLSM) using the fluorescent probe 5-carboxyfluorescein diacetate. The effect of ground on growth rate and reproduction of E. coli was performed in a grounded Petri dishes. Based on the undertaked studies it was found that the montmorillonite- based sorbent has no antibacterial and growth-boosting action against E. coli, while the sorbent effectively accumulates on the surface of live bacteria E. coli; in a combination of the sorbent with enrofloxacin, a bactericidal effectiveness of the latter against the E. coli decreased; antibacterial activity of enrofloxacin and it combinations with enriched montmorillonite containing sorbent to E. coli; the combination of enrofloxacin with the sorbent at the respective concentrations of 2, 1, 0.5 µg/ml and 4, 4, 2 mg/ml has bacteriostatic effect; enrofloxacin spectrum of a growth inhibition of E. coli increases with increasing the culture medium pH (from 6 to 8), but for doxycycline it reduces; a loss of size of growth inhibition zones of Escherichia coli due to enrofloxacin in acidic culture medium (pH 6) was at concentrations of sorbent from 2000 to 31,25 µg/ml in comparison with a control, such results were observed in neutral (pH 7) and alkaline culture medium (pH 8), but with the concentration of the sorbent from 2000 to 500 µg/ml; in 1.2 times more E. coli grows in grounded Petri dishes on a meat-and-peptone agar (MPA) than in ungrounded dishes.